1978
DOI: 10.1002/cpt197823173
|View full text |Cite
|
Sign up to set email alerts
|

A clinical safety trial of stroma‐free hemoglobin

Abstract: A stroma-free hemoglobin (SFH) solution was prepared which was sterile, pyrogen free, and contained only 1.2% of the stromal lipid present in unpurified hemolysate, 250 ml of which was administered slowly intravenously to 8 healthy men. Two control subjects received 250 ml of serum albumin. The SFH infusions were generally well tolerated by 7 of the 8 men. One subject developed abdominal pain and costovertebral angle tenderness after infusion, which disappeared within 48 hr. Bradycardia and a mild increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
145
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(149 citation statements)
references
References 3 publications
(5 reference statements)
1
145
0
3
Order By: Relevance
“…Early studies showed that transfusing stroma-free, unmodified, extracellular Hb into humans results in renal dysfunction, hypertension, and abdominal pain (87,94,126). Subsequent work indicated that free HbA tetramers dissociate into dimers when diluted into plasma.…”
Section: Engineering Principles For Rhboc Productsmentioning
confidence: 99%
“…Early studies showed that transfusing stroma-free, unmodified, extracellular Hb into humans results in renal dysfunction, hypertension, and abdominal pain (87,94,126). Subsequent work indicated that free HbA tetramers dissociate into dimers when diluted into plasma.…”
Section: Engineering Principles For Rhboc Productsmentioning
confidence: 99%
“…The early studies showed considerable side effects, most notably renal impairment due to vasoconstriction [75][76][77]. As a consequence, SHF has been abandoned as blood substitute.…”
Section: Stroma-free Haemoglobin (Sfh)mentioning
confidence: 99%
“…Nevertheless, several investigators described a continuous decrease in flow when perfusing kidneys with a SFH solution, with histology revealing hemoglobin deposits in the glomeruli [84] and tubules [9]. Other investigators confirmed these adverse effects on kidney function using ultrapure SFH, which was not observed with polymerized hemoglobins [44, 59,83, 981. Confirmation of the low-grade toxicity to the kidney using different purified and polymerized or cross-linked hemoglobin derivatives was obtained in several studies.…”
Section: Oxidative Metabolism During Warm Preservationmentioning
confidence: 99%